2017
DOI: 10.1063/1.4993206
|View full text |Cite
|
Sign up to set email alerts
|

Dual-gratings with a Bragg reflector for dielectric laser-driven accelerators

Abstract: The acceleration of a beam of electrons has been observed in a dielectric laser-driven accelerator (DLA) with a gradient of 300 MV/m. It opens the way to building a particle accelerator "on a chip" much more cheaply than a conventional one. This paper investigates numerically an efficient dielectric laser-driven accelerating structure, based on dual-gratings with a Bragg reflector. The design of the structure boosts the accelerating field in the channel, thereby increasing the accelerating gradient by more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…For the parameters discussed, the optimal Q-factors were shown to be around 150. Previous work on optimizing DLA structures for high acceleration gradient has shown that periodic dielectric mirrors may be useful in raising quality factors and field enhancement in DLA structures [39][40][41][42]. However, achieving DLA structures with these Q-factors may be difficult with current fabrication tolerances.…”
Section: Discussionmentioning
confidence: 99%
“…For the parameters discussed, the optimal Q-factors were shown to be around 150. Previous work on optimizing DLA structures for high acceleration gradient has shown that periodic dielectric mirrors may be useful in raising quality factors and field enhancement in DLA structures [39][40][41][42]. However, achieving DLA structures with these Q-factors may be difficult with current fabrication tolerances.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we demonstrate the flexibility for double grating DLA structures [19,20] to be driven using a laser system of wavelength shorter than the structure periodicity. If illuminated at normal incidence, the phase velocity FIG.…”
Section: Introductionmentioning
confidence: 99%
“…Towards this end, researchers have design, built, and power-tested a host of innovative photonic structures, demonstrating synchronous laser-electron interaction with fields up to 1.8 GV/m for relativistic electrons [2] and up to 370 MV/m for subrelativistic electrons [3]. Future structure proposals intend to improve field symmetry, damage handling, staging, diagnostics and more [4,5,6] But so far these devices have been operated in a 'test' configuration in which the drive laser propagates transversely to the electron beam, limiting the interaction region to the laser pulseduration. Since the dielectric lase accelerator (DLA) achieves high gradients by using short pulse lengths to avoid material damage, this necessarily limits the particle-wave interaction to a few microns (or limits the gradient [7]).…”
Section: Introductionmentioning
confidence: 99%